Plant growth promoting rhizobacteria enhances germination and bioactive compound in cucumber seedlings under saline stress - Pérez-García, Laura A; Sáenz-Mata, Jorge; Palacio-Rodríguez, Rubén; Rueda Puente, Edgar O.; Torres-Rodríguez , Juan Antonio; Preciado-Rangel, Pablo (Ecosistemas y Recursos Agropecuarios, 2025)
Soil salinity is a major abiotic stressor that negatively impacts agricultural productivity worldwide. One potential strategy to alleviate its effects is the use of plant growth-promoting rhizobacteria (PGPR). This study evaluated the impact of PGPR (Pseudomonas paralactis, Bacillus cereus, Sinorhizobium meliloti, and Acinetobacter radioresistens) on cucumber seedling (Cucumis sativus L.) growth under saline stress conditions (0, 5, 10, and 15% of NaCl). The results showed that PGPR biopriming significantly enhanced germination rates, plumule and radicle lengths, fresh and dry weights compared to non-inoculated controls. Notably, the highest germination rates were observed with P. paralactis and A. radioresistens at 81.20% and 79.39%, respectively, under saline stress. Additionally, PGPR inoculation enhanced chlorophyll content, proline accumulation, and antioxidant activity, indicating improved photosynthetic efficiency and osmotic adjustment under saline conditions. These findings suggest that PGPR inoculation is an effective, sustainable strategy for mitigating the detrimental effects of salt stress, improving cucumber seedling development. In order to increase the benefits of PGPR, further evaluations are being pursued using bacterial consortia to maximize individual effects and further improve plant growth under these conditions.